Faktor-Faktor yang Mempengaruhi Tax Avoidance Studi Empiris pada Perusahaan Sektor Energi dan Bahan Baku yang Terdaftar di BEI Periode 2022-2024 - Sari, Diana; Haninun, Haninun (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the influence of capital intensity, financial distress, and profitability on tax avoidance in energy and raw materials companies listed on the Indonesia Stock Exchange (IDX) for the 2022–2024 period. This study uses a quantitative approach with an associative research design. The data used are panel data obtained from company financial reports. The sampling technique used in this study was purposive sampling, with a total sample of 95 companies. Data analysis was performed using panel data regression with EViews 12 software. The results show that capital intensity, financial distress, and profitability have a negative effect on tax avoidance. This finding indicates that an increase in the proportion of fixed assets, a company's financial condition, and its ability to generate profits encourage higher levels of tax compliance. This study provides practical implications for company management in improving tax transparency and compliance, and for tax authorities in strengthening oversight, particularly in the energy and raw materials sector.